Capnodynamic assessment of mixed venous oxygen saturation - Anders Svedmyr (2025)
BackgroundMixed venous oxygen saturation (SvO2) is considered an important parameter for assessing the balance between oxygen supply and demand. Currently, obtaining SvO2 requires catheterization of the pulmonary artery which carries risks of adverse events and is technically demanding. For some patients, e.g. children, this approach may not be feasible or justified, necessitating less invasive monitoring alternatives. Capnodynamic monitoring has been proposed as a non-invasive alternative, but its accuracy and clinical applicability require further investigation. Furthermore, hemodynamic assessment in anesthetized and critically ill children remains challenging and, in this context, Capnodynamic cardiac output monitoring (COEPBF) and SvO2 (Capno-SvO2) could provide additional insight. The overall aim of this thesis was to investigate the accuracy and trending ability of Capno-SvO2 compared to pulmonary artery blood samples, in both experimental and clinical settings. In addition, COEPBF was compared to Esophageal Doppler in anesthetized children.MethodsIn study I, including anesthetized children, cardiac output measured by an Esophageal Doppler was compared to capnodynamic COEPBF during moderate hemodynamic interventions. Study II investigated the performance of Capno-SvO2 in comparison to blood gas CO-oximetry (Coox-SvO2) in anesthetized pigs undergoing major changes in oxygen delivery. Study III addressed the accuracy of Capno-SvO2 in a clinical context. Children undergoing anesthesia for cardiac catheterizations were included and Capno-SvO2 was compared to Coox-SvO2 during baseline conditions and moderate changes in oxygen delivery. Study IV, using a similar setup to study II, employed an experimental endotoxemia model to evaluate the performance of Capno-SvO2 under sepsis-like conditions. Across all studies, Bland-Altman analysis was used to determine the bias and agreement of absolute values between the modalities, while concordance analysis and four-quadrant plots were used to assess the ability of Capno-SvO2 to track physiological change.ResultsIn study I, the main finding was that the moderate reduction in cardiac output induced by increasing the positive end expiratory pressure (PEEP) was not detected by the esophageal doppler and did not noticeably alter the blood pressure. In contrast, the capnodynamic method recorded a 15 % reduction in cardiac output, consistent with previous, experimental findings. Study II-IV revealed an average bias of +1% to +3% between Capno-SvO2 and the reference method. In study II and III, limits of agreement were within the predefined acceptable range, while the spread of data points was slightly wider in study IV. The capnodynamic method demonstrated a high ability to track changes in SvO2, across all three studies.ConclusionsCapnodynamic assessment of SvO2 produced average values close to the reference method with limits of agreement within the predefined range of acceptance, even though the accuracy was negatively affected in the presence of sepsis. Capno-SvO2 reliably tracks changes in in both clinical and experimental settings. Furthermore, COEPBF tracked the moderate reduction in cardiac output caused by PEEP elevation in study I, not detectable by the established Esophageal Doppler. Capnodynamic monitoring of cardiac output and mixed venous oxygen saturation could offer valuable additional hemodynamic data in populations where pul- monary artery catheters are unavailable or not warranted. Being non-invasive, available also for small children, and easy to set up makes it particularly appealing for pediatric anesthesia practice, though certain limitations need to be considered. Further clinical trials are mandated to determine the role of capnodynamic monitoring in the intensive care setting.List of scientific papersI. Cardiac Output Assessments in Anesthetized Children: Dynamic Capnography Versus Esophageal Doppler. Jacob Karlsson, Anders Svedmyr, Marion Wiegele, Per-Arne Lönnqvist, Mats Wallin, Magnus Hallbäck Anesth Analg. 2022 Mar 1;134(3):644-652. https://doi.org/10.1213/ane.0000000000005679II. Non-invasive capnodynamic mixed venous oxygen saturation during major changes in oxygen delivery. Anders Svedmyr, Mark Konrad, Mats Wallin, Magnus Hallbäck, Per-Arne Lönnqvist, Jacob Karlsson. J Clin Monit Comput. 2022 Oct;36(5):1315-1324. https://doi.org/10.1007/s10877-021-00762-5III. Validation of a Novel Method for Noninvasive Mixed Venous Oxygen Saturation Monitoring in Anesthetized Children. Anders Svedmyr, Kristoffer Steiner, Andreas Andersson, Gunnar Sjöberg, Magnus Hallbäck, Mats Wallin, Per-Arne Lönnqvist, Jacob Karlsson. Anesth Analg. 2024 Oct 1;139(4):781-788. https://doi.org/10.1213/ane.0000000000007083IV. Capnodynamic assessment of mixed venous oxygen saturation in a porcine experimental endotoxemic model. Anders Svedmyr, Joakim Hedov, Miklos Lipcsey, Mats Wallin, Magnus Hallbäck, Per-Arne Lönnqvist, Jacob Karlsson. Scientific Reports. 2024 Nov 5;14(1):26807. https://doi.org/10.1038/s41598-024-77483-7